A comparative ToF-SIMS and GC–MS analysis of phototrophic communities collected from an alkaline silica-depositing hot spring. (July 2017) - Siljeström, S.; Parenteau, M.N.; Jahnke, L.L.; Cady, S.L.
Highlights: ToF-SIMS and GC–MS analyses of phototrophs in a silica-depositing hot spring. To interpret the ToF-SIMS data, samples of increasing complexity were analyzed. A ToF-SIMS lipid database was constructed. This database will be used for the analysis of modern and fossilized microbial mats. ToF-SIMS detected particular lipids and mapped them to cells in the mat. Abstract: One of few techniques that is able to spatially resolve chemical data, including organic molecules, to morphological features in modern and ancient geological samples, is time-of-flight secondary ion mass spectrometry (ToF-SIMS). The ability to connect chemical data to morphology is key for interpreting the biogenicity of preserved remains in ancient samples. However, due to the lack of reference data for geologically relevant samples and the ease with which samples can be contaminated, ToF-SIMS data may be difficult to interpret. In this project, we aimed to build a ToF-SIMS spectral database by performing parallel ToF-SIMS and gas chromatography–mass spectrometry (GC–MS) analyses of extant photosynthetic microbial communities collected from an alkaline silica-depositing hot spring in Yellowstone National Park, USA. We built the library by analyzing samples of increasing complexity: pure lipid standards commonly found in thermophilic phototrophs, solvent extracts of specific lipid fractions, total lipid extracts, pure cultures of dominant phototrophic community members, and unsilicified phototrophic streamer communities. The results showed that important lipids and pigments originating from phototrophs were detected by ToF-SIMS (e.g., wax esters, monogalactosyldiacylglycerol, digalactosyldiacylglycerol, sufloquinovosyldiaglycerol, alkanes, etc.) in the streamer lipid extracts. Many of the lipids were also detected in situ in the unsilicified streamer, and could even be spatially resolved to individual cells within the streamer community. Together with the ToF-SIMS database, this mapping ability will be used to further explore other microbial mats and their fossilized counterparts in the geological record. This is likely to expand the geochemical understanding of these types of samples.